2017
DOI: 10.1080/07448481.2017.1312415
|View full text |Cite
|
Sign up to set email alerts
|

Illness uncertainty and illness intrusiveness as predictors of depressive and anxious symptomology in college students with chronic illnesses

Abstract: Compared to peers with asthma or allergies, college students with other chronic illnesses reported higher levels of anxious symptoms. Illness uncertainty and intrusiveness appear to be predictors of psychological distress, regardless of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 52 publications
6
47
0
Order By: Relevance
“…daily routines to time-consuming treatments (between 2 or 3 hours a day) can also have a negative impact on emotional well-being, leading to the appearance of a depressive clinical profile, as shown in our results and those of previous studies [10]. We found no differences between patients with PCD and their healthy peers, as compared to other studies [12,13,15], and observed that depressive symptomatology is more present in healthy people and anxious symptomatology in PCD.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…daily routines to time-consuming treatments (between 2 or 3 hours a day) can also have a negative impact on emotional well-being, leading to the appearance of a depressive clinical profile, as shown in our results and those of previous studies [10]. We found no differences between patients with PCD and their healthy peers, as compared to other studies [12,13,15], and observed that depressive symptomatology is more present in healthy people and anxious symptomatology in PCD.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, this vital period of changes can have a negative impact on their image of themselves, since approximately 40% of the whole sample showed low levels of self-esteem. Second, with regard to emotional symptomatology, the predominant psychopathological clinical feature is anxiety in PCD, which is most characteristic in respiratory diseases [10,16]. Uncertainty about the future, fears (of deterioration, respiratory exacerbations, fertility problems in adulthood, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should consider and address these inconsistencies in an attempt to establish a firm understanding and grounding knowledge of grit’s applications to certain success-related outcomes. It is identified that the mental well-being may influence not only factors determining our perceptions, thoughts, and behaviors, but also our physiological wellbeing (Huppert, 2009; Mullins et al, 2017). This study aims to include a mental well-being measure as a variable which will address the need of exploring the relationship between grit and psychological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Some students who suffer from a chronic illness have anxiety [27]. For example, a student who suffers diabetes is required to take daily insulin injections and go to Anxiety Disorders the health center, and some may experience dizziness while at the university campus.…”
Section: Illnessmentioning
confidence: 99%